Bark development: Comparative study of two Ceiba (Malvaceae) species - Guía-Ramírez, Sandra; Terrazas Salgado, Teresa Margarita; Aguilar Rodríguez, Silvia; Yáñez-Espinosa, Laura; Tejero-Díez, José Daniel (Instituto de Ecología, A.C., 2020)
Background and Aims: Ceiba aesculifolia and C. pentandra (Malvaceae) are two of the four Ceiba species growing in Mexico. They are recognized as "pochotes" and have ornamental and medicinal use of their bark. In order to find distinctive attributes between these species of wide distribution in the country, a comparative study of the anatomical structure of the bark along its axes and the relationship with possible ecological adaptations were carried out. Methods: Samples from the new branches to the main trunk of four individuals were collected from the deciduous tropical forest of the State of Mexico and Puebla. Histological sections of the bark were cut with sliding microtome; the sections were stained with safranine-fast green and mounted in synthetic resin. Key results: The bark is slightly fissured to fissured on mature stems, leaden-gray color in C. aesculifolia and green in C. pentandra; with prickles. The peridermis originates from a subepidermal layer at the branch tips; as the axes increase in diameter, the rays strongly dilate (wedge-shaped) and the phloem fibers are organized in strata, characteristics shared with other Bombacoideae (Malvaceae). Ceiba pentandra maintains patches of peridermis that are alternate with epidermis, unstratified prickles and few druses (<20/mm2), while in C. aesculifolia there is a rhytidome, stratified prickles, and abundant druses (50-60/mm2). Conclusions: Details of structural changes along the axis, in addition to the differences found between both species are reported for the first time for Ceiba. The rapid differentiation of the peridermis in the ceibas studied is interpreted as an adaptation to protect against sunlight and desiccation; an aspect that has been observed in other species growing in seasonal environments.